PENERAPAN METODE FUZZY LOGIC DENGAN MODEL TAHANI APLIKASI TIKTOK TERHADAP PRILAKU MASYARAKAT - Rizal Rachman; Olsen Zendrato; Agung Tri Retnowati (STMIK Mardira Indonesia, Bandung, 2021)
Nowadays, the existence of social media is a necessity for humans. Social media is currently the most effective and suitable intermediary in disseminating information quickly and easily. Social media is one of the media that is widely used by modern humans to communicate and disseminate information in personal or group form. One of the social media during this pandemic is Tiktok. According to Kompas.com, TikTok social media has also become one of the most popular applications during 2020. Based on data from Apptopia, the TikTok application became the most downloaded application in 2020. In total there are 850 million downloads. The main purpose of this study is to find out how much influence the use of TikTok has on people's behavior. This study uses the Fuzzy Logic method with the Tahani model. The results of the analysis using fuzzy logic obtained the results that the influence of social media in society with a certainty level of 85%. After processing fuzzy data, conclusions will be drawn from this, namely the influence of social media on people's behavior.Keywords: TikTok, social media, Fuzzy LogicDOI: 10.5281/zenodo.5807716